The biomarkers of oxidative stress in young cross-country skiers - Karvonen, H.; Kallio, T.; Tervo, P.; Mäki, M.; Käsmä, J.; Kilpeläinen, P.; Virtanen, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Oxidative stress is characterized by an imbalance between antioxidants and oxidizing species of the body. Increased production of free radicals overwhelms antioxidant defenses resulting in cellular damage and oxidation of biomolecules (Wood et al. 2006). In athletes, prolonged exercise and physical stress lead to increased levels of oxidative stress indicators in blood. It may be seen as reduced performance, tissue damage and even overtraining syndrome if recovery periods are not sufficient (Finaud et al. 2006). Oxidative stress can be quantified by measuring metabolites formed by oxidation. Several metabolites have been introduced in the literature, such as the carbonyl groups, isoprostanes and 8- hydroxydeoxyguanosine (8-oxodG) which can be used to estimate the oxidation of proteins, lipids and DNA, respectively. In addition, the amount of reactive oxygen species (ROS) or the antioxidant potential can be assayed (Wood et al. 2006).